Characteristics of genomic alterations of lung adenocarcinoma in young never‐smokers. Issue 7 (7th May 2018) - Luo, Wenxin; Tian, Panwen; Wang, Yue; Xu, Heng; Chen, Lu; Tang, Chao; Shu, Yang; Zhang, Shouyue; Wang, Zhoufeng; Zhang, Jun; Zhang, Li; Jiang, Lili; et al.
Abstract : Non‐small‐cell lung cancer (NSCLC) has been recognized as a highly heterogeneous disease with phenotypic and genotypic diversity in each subgroup. While never‐smoker patients with NSCLC have been well studied through next generation sequencing, we have yet to recognize the potentially unique molecular features of young never‐smoker patients with NSCLC. In this study, we conducted whole genome sequencing (WGS) to characterize the genomic alterations of 36 never‐smoker Chinese patients, who were diagnosed with lung adenocarcinoma (LUAD) at 45 years or younger. Besides the well‐known gene mutations (e.g., TP53 and EGFR ), our study identified several potential lung cancer‐associated gene mutations that were rarely reported (e.g., HOXA4 and MST1 ). The lung cancer‐related copy number variations (e.g., EGFR and CDKN2A ) were enriched in our cohort (41.7%, 15/36) and the lung cancer‐related structural variations (e.g., EML4‐ALK and KIF5B‐RET ) were commonly observed (22.2%, 8/36). Notably, new fusion partners of ALK ( SMG6‐ALK ) and RET ( JMJD1C‐RET ) were found. Furthermore, we observed a high prevalence (63.9%, 23/36) of potentially targetable genomic alterations in our cohort. Finally, we identified germline mutations in BPIFB1 (rs6141383, p.V284M), CHD4 (rs74790047, p.D140E), PARP1 (rs3219145, p.K940R), NUDT1 (rs4866, p.V83M), RAD52 (rs4987207, p.S346*), and MFI2 (rs17129219, p.A559T) were significantly enriched in the young never‐smoker patients with LUAD when compared with the in‐house noncancer database ( p < 0.05). Our study provides a detailed mutational portrait of LUAD occurring in young never‐smokers and gives insights into the molecular pathogenesis of this distinct subgroup of NSCLC. Abstract : What's new? Young patients with non‐small‐cell lung cancer (NSCLC) represent a distinct disease entity: they are often female, never smoked and usually present with lung adenoma carcinomas. Here the authors performed whole‐genome sequencing in patients with early‐onset NSCLC who never smoked and find an overall lower mutation burden and fewer classic driver substitutions. However, oncogenic fusions were found more frequently, underscoring that a unique molecular make‐up defines this specific subgroup of cancer patients.